Settings for Copies of Deeds Issued by Notaries in Agreements Between Indonesian Citizens and Foreign Citizens - ANJANI, Mey; BUDIARTHA, I Nyoman Putu; RENAYA, Nengah (Journal of Political And Legal Sovereignty, 2024)
Purpose:Analyze the arrangements for copies of deeds issued by notaries in agreements between Indonesian citizens and foreign citizens, the validity of the copy of the deed and the legal consequences of copies of the deed in Indonesian and foreign languages which do not comply with the minutes of the deed.Methodology:The type of research used in this study is a type of normative legal research oriented to the absence of norms, conflicting norms and vagueness of norms. When associated with this study, this Normative research method leads to the vagueness of norms that regulate copies of deeds issued in Indonesian and foreign languages.Findings:Notaries are required to prepare minutes of the deed as a protocol and provide a copy of the deed to interested parties. In an Indonesian-foreigner agreement, a notary must ensure the legality of the copy in accordance with the law so that it still has evidentiary force. Minutes of the deed can be void by law (Nietig van Rechtswege) if they do not meet the formal requirements as an authentic deed or can be canceled (Vernietigbaar) if they do not meet the material requirements.Implication:Provide readers with an understanding of the regulation of copies of deeds issued by notaries in agreements between Indonesian citizens and foreign citizens and legal developments, especially for notaries, regarding the validity of copies of deeds and the legal consequences of copies of deeds in Indonesian and foreign languages that do not comply with the minutes of the deed.